Assessment of H2S and BTEX concentrations in ambient air using passive sampling method and the health risks - Ulutas, Kadir; Kaskun, Songul; Demir, Selami; Dincer, Faruk; Pekey, Hakan (SPRINGER, 2021)
Wastewater treatment plants (WWTPs) may be a source of nuisance in neighbouring places due to hydrogen sulphide (H2S) and BTEX (benzene, toluene, ethylbenzene, and xylenes) emissions. In this study, samples were collected from WWTP workplace ambient air and outdoor ambient air around one of the largest WWTPs in Istanbul with a capacity of 250,000 m(3)/day to evaluate the effects of H2S and BTEX emissions. Samples were collected in three seasons for 15-day durations: winter (November 2015), spring (May 2015), and summer (August 2016). Average concentrations of H2S and BTEX were determined as 1.1 and 56.2 mu g/m(3), respectively. Average concentrations BTEX components were 4.9, 20.7, 6.4, and 24.2 mu g/m(3), respectively. Health risk assessment for plant workers and local residents was performed for H2S and BTEX inhalation exposure using the method by USEPA. Results show that H2S and BTEX emissions do not have harmful effects on human health.
Keywords: Wastewater treatment plant; Passive sampling; H2S; BTEX; Health risk; VOLATILE ORGANIC-COMPOUNDS; PHOTO-CATALYTIC-OXIDATION; HYDROGEN-SULFIDE; LANDFILL SITE; BENZENE; TOLUENE; VOC; Environmental Sciences & Ecology